Isu Gender dalam Buku Bergambar Matematika Rancangan Calon Guru Sekolah Dasar - Zetra Hainul Putra; Gustimal Witri; Syahrilfuddin Syahrilfuddin (Jurnal Elemen, 2019)
This study aims to analyse the gender issue presented in pre-service elementary teacher-designed mathematics picture books (BBM). Thirteen BBMs are analysed based on male and female characters presented in the titles, pictures in the cover, main characters, and a number of pictures, conversations, and words in book contents. The findings show that the male characters are presented 1.79 times more often than the female characters. The numbers of pictures, conversations, and words in the book contents for males is 1.79; 1.99; and 1.79 consecutively times more often than the female characters. Meanwhile, each of the two BBMs presents only male or female characters. The implications of this study indicate that gender is still an important issue in BBM being developed.